2013
DOI: 10.3390/ijms140715017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Static Magnetic Fields and Fluoride Ions on the Antioxidant Defense System of Mice Fibroblasts

Abstract: The results of studies on the biological influence of magnetic fields are controversial and do not provide clear answers regarding their impact on cell functioning. Fluoride compounds are substances that influence free radical processes, which occur when the reactive forms of oxygen are present. It is not known whether static magnetic fields (SMF) cause any changes in fluoride assimilation or activity. Therefore, the aim of this work was to determine the potential relationship between magnetic field exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…This leads to spontaneous depolarization of the cells, mainly through the influence of calcium channels [Morgado‐Valle et al, ; Zmyślon, ]. There are limited data supporting the antioxidant effect of ELF‐EMF, in particular its positive impact on improving the functioning connective tissue's cells [Sosnowski et al, ; Kurzeja et al, ]. We have observed an increase of SOD activity in the hemolysate, with results that are consistent with data presented by Rauš Balind et al [].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This leads to spontaneous depolarization of the cells, mainly through the influence of calcium channels [Morgado‐Valle et al, ; Zmyślon, ]. There are limited data supporting the antioxidant effect of ELF‐EMF, in particular its positive impact on improving the functioning connective tissue's cells [Sosnowski et al, ; Kurzeja et al, ]. We have observed an increase of SOD activity in the hemolysate, with results that are consistent with data presented by Rauš Balind et al [].…”
Section: Discussionsupporting
confidence: 90%
“…Those authors demonstrated that ELF‐EMF decreased the level of oxidative stress in gerbil brains with induced global cerebral ischaemia, as demonstrated by amplified SOD activity [Rauš Balind et al, ]. Studies on mouse fibroblasts conducted by Kurzeja et al [] showed a reduced level of oxidative stress markers, and normalization of the activity of SOD, GPx, and CAT enzymes, as well as a change of energy state in fibroblasts. In contrast, Sosnowski et al [] observed a decrease in the concentration of H 2 O 2 , without any irregularities in the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…They found that SMF significantly reduced oxidative stress and normalized the activities of antioxidant enzymes, including superoxide dismutase (SOD). In addition, their results indicated that SMF exposure positively affected the malondialdehyde (MDA) concentrations (Kurzeja et al 2013). Similar results were also reported by several other authors (Buyukuslu et al 2006, Polita ń ski et al 2010, Ghodbane et al 2013, Omonkhua and Abajingin 2013.…”
Section: Declaration Of Interestsupporting
confidence: 68%
“…Evaluation of lipid peroxidation in cell cultures exposed to SMF was performed by Kurzeja et al (2013). They found that SMF significantly reduced oxidative stress and normalized the activities of antioxidant enzymes, including superoxide dismutase (SOD).…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…Kurzeja et al [] found that 0.4, 0.6, and 0.7 T moderate intensity SMFs could rescue fluoride‐induced ATP decrease in fibroblasts. In addition, the effect was magnetic field intensity‐dependent, in which 0.7 T SMF produced more significant effects than 0.4 and 0.6 T SMFs [Kurzeja et al, ]. However, Zhao et al [] used 8.5 T strong homogeneous SMF to test its effect in three cell lines, including human‐hamster hybrid A(L) cells, mitochondria‐deficient (ρ 0 A(L)) cells, and DNA double‐strand break (DSB) repair‐deficient (XRS‐5) cells.…”
Section: Introductionmentioning
confidence: 99%